2002
DOI: 10.1093/ajcn/75.5.914
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding protects against celiac disease

Abstract: The gradual introduction of gluten-containing foods into the diet of infants while they are still being breast-fed reduces the risk of celiac disease in early childhood and probably also during the subsequent childhood period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
364
6
13

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(392 citation statements)
references
References 32 publications
9
364
6
13
Order By: Relevance
“…34 Also, a higher frequency of terminated breast feeding before the gluten introduction in children with diagnosed CD versus controls was found. 35 The question whether these environmental factors are affecting the phenotype (ie, the intensity of the symptoms), and thus, the chance of being diagnosed rather than triggering the onset of the disease has been under debate. 36 For genetic issues it is often of interest to compare epidemiological data between different regions, countries and populations.…”
Section: Epidemiology Population Geneticsmentioning
confidence: 99%
“…34 Also, a higher frequency of terminated breast feeding before the gluten introduction in children with diagnosed CD versus controls was found. 35 The question whether these environmental factors are affecting the phenotype (ie, the intensity of the symptoms), and thus, the chance of being diagnosed rather than triggering the onset of the disease has been under debate. 36 For genetic issues it is often of interest to compare epidemiological data between different regions, countries and populations.…”
Section: Epidemiology Population Geneticsmentioning
confidence: 99%
“…Coeliac disease is induced by prolamines (gluten) present in wheat, barley or rye [4] in genetically susceptible individuals. Timing of the introduction of gluten into the infant diet, the amount of gluten consumed and the introduction of gluten after cessation of breast-feeding have been linked to the risk of coeliac disease and type 1 diabetes [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Ivarsson et al found that children with CD received larger initial amounts of flour compared to controls. 3 Another mechanism through which breast milk could protect against CD is by preventing gastrointestinal infections in the infant. Breast milk is known to significantly protect against a number of infections including gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case-control study, Ivarsson et al examined whether breast feeding and the mode of introduction of gluten influenced the risk of CD in 627 Swedish children with CD compared with 1254 controls. 3 They found that the risk of the disease was reduced in children if they were breast feeding at the time of introduction of dietary gluten. Peters et al 4 and Auricchio et al 5 also showed that breast feeding was associated with a reduced risk of developing childhood CD.…”
mentioning
confidence: 99%